Education as a Predictor Factor for Knowledge of COVID-19 in Portugal - Gomes da Silva, Joana; Silva, Carla Sofia; Alexandre, Bárbara; Morgado, Pedro (Frontiers in Public Health, 2021)
Introduction/Objective: Pandemic of COVID-19 is a major public health problem. At the time of development of this study, no specific medication/vaccine for this disease was approved. Therefore, preventive measures were the main key to control this pandemic. Health literacy (HL) is the ability to obtain, understand and use the information to make free and informed decisions about the health of an individual and to promote community empowerment. Thus, the HL of COVID-19 is important for community empowerment and the adoption of preventive measures. This article aims to understand possible predictors of HL of COVID-19, functional domain. Material and Methods: A cross-sectional study was designed, applying the Questionnaire of COVID-19 (previously designed and submitted to a preliminary pilot testing) through an online platform from April 23 to June 23, 2020. An Index of Health Knowledge of COVID-19 Questionnaire (IHK-COV19) was constructed. Associations between independent variables (“Gender,” “Age,” “Education,” and “Risk Factor” for COVID-19 codified by ICPC-2) and HL were assessed using multivariate analyses (mixed effects models). The level of significance was set at p < 0.05. Results: Our sample includes 864 subjects (median age, 44.33 years), mostly women (n = 619; 71.76%), undergraduate (n = 392; 45.37%) and with at least one risk factor for COVID-19 (n = 266; 30.79%). Univariate and multivariate analyses demonstrated “Age” as a negative predictor of IHK-COV19 and “Education” and “Risk Factor” as positive predictors of IHK-COV19. Conclusions: Health knowledge regarding COVID-19 is associated with the level of education. Future interventions should consider including HL mechanisms in interventions designed to improve communication.